the Evaluasi Pelaksanaan Pembelajaran Mata Pelajaran Dasar Perancangan Teknik Mesin Di SMK Muhammadiyah Prambanan Sleman Dalam Masa Pandemi Covid-19 - yoga arie wibawa; rabiman; Arif Bintoro Johan; Adhy Pratomo Yunianto Herlambang (JURNAL VOKASI DEWANTARA (JVD), 2024)
Abstract: This research aims to evaluate the implementation of learning progress during pandemic Covid-19 in subject Basic Design Mechanical Engineering at SMK Muhammadiyah, Prambanan, Sleman, based on: (1) Understanding the objectivities of online learning during pandemic Covid-19, (2) Availability of facilities, media, and online learning facilities, (3) Factors that affect the online learning process, (4) Effectiveness of online learning. This research involved a quantitative research with data collection technique using questionnaires or questionnaires based on the CIPP evaluation model (context, input, process, product) for students of SMK Muhammadiyah Prambanan with majoring in Mechanical Engineering consisting of 59 students. The results of the CIPP evaluation research show that the score obtained from the context aspect is 75 % categorized in the medium level, the input aspect is 79% categorized in the medium level, the process aspect is 72% categorized in the medium level, product aspect with 73% categorized in the medium level. From the score obtained for each aspect, the average overall aspects are 75%, which means that all aspects still need to be improved to get maximum result. Keywords: Evaluation of Learning Implementation; Pandemic Covid-19; and Basic Design of Mechanical Engineering Class X.